An application for paraphrasing assisted by artificial intelligence to reduce plagiarism levels in multilingual academic writing - Nursaid Nursaid; Yenni Hayati; Tressyalina Tressyalina; Ella Wulandari; Bima Mhd Ghaluh (BAHASTRA, 2026)
This research focuses on creating and evaluating the efficacy of Languafrasa aimed at decreasing plagiarism rates in student essays. Beyond lowering similarity scores, the study positions Languafrasa as an educational writing companion that helps students compare alternative expressions, preserve meaning, and practise responsible paraphrasing in Indonesian academic writing. Languafrasa is designed to incorporate AI-powered paraphrasing functionalities in Indonesian and 102 other languages. The study followed an experimental design involving 30 students who were divided into two groups. One group used conventional essay writing methods, while the other utilized the Languafrasa application. The experimental outcomes revealed a significant decrease in plagiarism levels among students using the Languafrasa application. Additionally, students in the experimental group demonstrated higher efficiency than those in the control group. Feedback from the questionnaire administered to all participants corroborated these results, with most students favoring the application over traditional writing methods. Users found Languafrasa enjoyable, user-friendly, and an effective aid in essay-writing instruction. These findings suggest that Languafrasa contributes not only to textual originality but also to students' confidence and engagement in learning how to paraphrase. The application is accessible at https://languafrasa.com.